Product innovation strategies: a firm level analysis - DÜZGÜN ÖNCEL, BURCU (My University, 2022)
In this study, we examine the association between firms’ innovation process and their product quality improvement and new product introduction strategies. Our focus is on the distinction between firms’ product quality improvement and variety extension objectives. We use data from Turkish Statistical Institute (TURKSTAT) Innovation Survey between the years 2014 and 2016. According to the descriptive results, number of firms report that product quality as very important is greater than the firms report that product variety. Logit estimations results show that majority of the product variety objective and technology level indicators are significant and positively related with probability of product innovation. There is also a positive relationship between probability of product innovation and patent applications for small and medium sized firms. Moreover, probability of innovation is positively related with variety objective whereas quality objective indicators are insignificant.

Bu çalışmada, firmaların yenilik süreci ile ürün kalite iyileştirme ve yeni ürün tanıtım stratejileri arasındaki ilişkiyi inceliyoruz. Odak noktamız, firmaların ürün kalitesini iyileştirme ve çeşitlerini genişletme hedefleri arasındaki ayrımdır. Türkiye İstatistik Kurumu (TÜİK) Yenilik Araştırması'nın 2014-2016 yılları arasındaki verilerini kullanıyoruz. Tanımlayıcı sonuçlara göre ürün kalitesinin önemli olduğunu bildiren firmarların sayısı ürün çeşitliliğinden daha fazladır. Logit tahmin sonuçları ise, ürün çeşitliliği hedef göstergelerinin çoğu ve teknoloji seviyesi, firma türleri için ürün yeniliği olasılığı ile anlamlı ve pozitif olarak ilişkilidir. Firmaların patent başvuruları ile küçük ve orta ölçekli firmalar için ürün yeniliği olasılığı arasında pozitif bir ilişki olduğunu göstermektedir. Ayrıca, Çeşitlilik hedefi ile yenilik olasılığı artarken, kalite hedefi ile ilgili göstergeler anlamsızdır
Ürün yenilik stratejileri: Firma düzeyi analizi
Keywords: Innovation objectives; product innovation; logit analysis; Yenilik hedefleri; ürün yeniliği; logit analizi